Nilai Pendidikan Karakter dalam Novel Tahun-tahun yang Hilang Berdiri Tegar di Bawah Bayang-bayang Syekh Yusuf Karya Rully Ferdiansyah - Muhammad Israq; Usman Usman; Sakinah Fitri (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
This research is a qualitative research with descriptive analysis method which aims to describe: (1) the socio-historical background of Rully Ferdiansyah as the author of the novel Years of the Lost Standing Strong in the Shadows of Sheikh Yusuf and (2) the value of character education contained in novel The Lost Years Standing Strong in Shaykh Yusuf's Shadow. The primary data of this research is the novel Years of the Lost Standing Strong in the Shadow of Sheikh Yusuf, while the secondary data of this study was obtained through a written interview with Rully Ferdiansyah as the author of the novel. The source of the data for this research comes from the novel Years of the Lost Standing Strong in the Shadows of Sheikh Yusuf and a written interview with Rully Ferdiansyah as the author of the novel. Data collection was carried out in three stages, namely reading techniques, note-taking techniques, and interview techniques. The data that has been obtained is then analyzed through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. This research uses the theory of sociology of literature by Rene Wellek and Austin Warren. The results of the study show that (1) Rully Ferdiansyah as the author of the novel Years of the Lost Standing Strong in the Shadows of Sheikh Yusuf was born in Serang, Banten, precisely on August 30, 1985. Rully Ferdiansyah is of Sunda-Banten ethnicity and adheres to the teachings of Islam. The author is an environmental activist and anti-social disease activist in Cilegon. In addition, the author is a demisioner at the Banten Arts Council for the 2017-2018 period in the literary committee and also as a functionary of ICMI Banten for the 2019-present period, (2) In the novel Years of the Lost Standing Strong in the Shadows of Sheikh Yusuf, it is found five main characters in accordance with the provisions of the Ministry of Education and Culture which include: religiosity values (20.68%), integrity values (16.37%), nationalist values (11.20%), independent values (10.34%), and mutual cooperation value (6%). The value of integrity, which is the fifth value, in this novel is in second place under the value of religiosity